Fluorescence lifetime imaging ophthalmoscopy adds the retina to cortical pathology for visual dysfunction in neurodegenerative diseases - Nimworaphan, Jirat; Markowitz, Daniel M.; Sergott, Robert C. (Frontiers in Neurology, 2025)
Because neurodegenerative diseases such as Parkinson’s and Alzheimer’s Diseases [AD and PD] as well as the progressive forms of multiple sclerosis [MS] are invariably associated with clinically significant cortical symptoms such as language difficulties, motor skill deficits and cognitive impairments, especially memory, a tacit assumption evolved that visual disorders related to cortical dysfunction must localize only to the temporal, parietal and occipital lobes. Based upon our current understanding, retinal changes in MS are most likely secondary to optic neuropathy, whereas in AD and PD, they appear to represent primary retinal changes. The paradigm was reinforced by the lack of retinal findings using ophthalmoscopy. Spectral domain optical coherence tomography [OCT], optical coherence angiography [OCT-A], and fundus autofluorescence [FAF] have challenged this creed by uncovering structural changes within the retina over and above what can occur as a consequence of optic neuropathy in the case of MS. Still, definitive diagnostic and prognostic data have yet to emerge. Fluorescence lifetime imaging ophthalmoscopy [FLIO], a non-invasive, non-contact, painless imaging technology, measures nanosecond lifetimes of endogenous retinal fluorophores, some of which are linked to mitochondrial activity. Therefore, FLIO is a metabolic, not a structural imaging modality. Because mitochondrial dysfunction occurs in many neurodegenerative diseases, FLIO offers a unique strategy for investigating retinal metabolism in AD, PD, and MS. This article reviews the basic biomedical engineering of FLIO and reports preliminary data from these diseases, correlated with disease duration. These functional in vivo data are consistent with retinal metabolic changes in AD, PD, and progressive MS that were “hiding in plain sight” from structural examinations.